Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan Melalui Disiplin Kerja Sebagai Variabel Intervening - Aditya Hendrawan; Ari Pradhanawati (Universitas Diponegoro, 2017)
In the year 2011 through 2015, PT Cassanatama Naturindo have a disturbance of their business development, mainly on their sale per year and absence of their worker. According of the retreived data, there is effect between worker absence and their sales ups and down compared of their target that must accomplished. So, from that fact researcher can see that there is relation between work motivation, work satisfaction, and work discipline with worker performance.This study aims to determine the effect of work motivation and work satisfaction towards worker performance thru work discipline as intervening variable. Type of explanatory research, data collection techniques are interviews with the tool questionnaire, sampling technique purposive sampling with a sample size 95 of PT Cassanatama Naturindo Semarang Workers. The data were analyzed through software SPSS.The result showed work motivation towards work discipline have affect with t score > t table. The effect work satisfaction with work discpline have affection t score > t table. Effect of work motivation and work satisfaction towards work discipline with F score > F table, effect work motivation towards worker performance with t score > t table, effect of work satisfaction toward worker performance with t score > t table, effect of work discipline towards work performance with t score > t table, effect of work motivation, work satisfaction, and work discipline towards work performance with F score > F table. Fairly, based of sobel test, work motivation affecting worker performance thru work discipline, have t score > t table, and work satisfaction affecting worker performance thru work discipline have t score > t table.In Conclusion, all of independent variables of this study have affect towards dependent variables, either partially or simultan, thus work motivation which affecting worker performance thru work discipline occured partial mediation, and work satisfaction variable with worker performance thru work discipline occured partial mediation. Reseacher suggest, on increasing worker performance, company must expressly correcting accuracy of employee to producing consistent with company standard. Dividing job must consistently with employee skill so that they can work as maximize, and then company could afford training for their workers, increase salary, and concern of recruitment education.